Mobilizing credit for clean energy: De-risking and public loan provision under learning spillovers - Paul Waidelich; Joscha Krug; Bjarne Steffen (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Policymakers regularly rely on public financial institutions and government bodies to provide loans to clean energy projects. However, the market failures that public loan provision addresses and the role it can play in a policy strategy that also features de-risking measures, such as interest rate subsidies, remain unclear. Here, we develop a model of banks providing loans to clean energy projects that use a novel technology. Early-stage loans build up financing experience that spills over to peers and hence is undersupplied by the market. In addition to this cooperation problem, bankability requirements can result in a coordination failure where the banking sector remains stuck in an equilibrium with no loans for the novel technology, although a preferable equilibrium with loans exists. Public provision of early-stage loans is inferior to de-risking instruments when solving the cooperation problem because it crowds out private banks' loan provision. However, public loan provision can more effectively resolve the coordination failure by pushing the banking sector to a better equilibrium, ideally in combination with additional de-risking measures to internalize learning spillovers.
Keywords: G21; H81; Q48; Q55; 330; Energy transition; state investment bank; government loans; credit guarantees; multiple equilibria